The relationship between university students’ perception of boredom in leisure time and internet addiction during social isolation process - Satılmış, Sinan Erdem; Cengiz, Recep; Güngörmüş, Hamdi Alper (Journal of Dependence, 2023)
Objective: The aim of the study is to examine the relationship between university students’ perception of leisure time boredom and internet addiction levels during the social isolation process and to compare them in terms of various demographic variables. Method: The universe of research exists students who continue their education at Manisa Celal Bayar University. The sample group consists of a total of 503 volunteers, 296 females and 207 males selected by convenience sampling method. Additionally the personal information form, the "Young Internet Addiction Test-Short Form" (YIAT-SF) and the "Leisure Boredom Scale" (LBS) were applied to the participants. Results: University students had average scores for YIAT-SF (2.67±0.88), boredom (2.66±1.11) and dissatisfaction (2.50±0.97). In addition, there was a positive and significant relationship between YIAT-SF and LBS’s subscales, while the level of boredom significantly affected internet addiction and it was found to predict with a variance of 41%. Conclusion: The perception of boredom in leisure significantly affects the internet addiction levels of individuals. As the perception of boredom in leisure increases in the social isolation process of university students, the level of internet addiction also increases.